Digital Transformation in Enterprise Europe Network: Comparative Analysis of Online and Traditional Promotional Events - Suder, Marcin; Gródek-Szostak, Zofia; Adamczyk, Jadwiga; Dubiel, Nina; Wiktor, Kamil (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
The COVID-19 pandemic forced businesses to adapt to new conditions, affecting technology transfer networks, including the largest, the Enterprise Europe Network (EEN). The study aimed to compare the effectiveness of events organized by the EEN network in online and traditional formats. The analysis utilized data from all promotional events organized by EEN from 2020-2021. Several different measures of effectiveness were adopted, primarily referring to the number of meetings, the number of interested parties, and the number of entities that started cooperation. The results showed that online events were more effective than traditional ones, generating more meetings and signed agreements. These statistically significant results suggest that moving activities to the virtual space can be an effective model for future EEN activities. The research and results contribute significantly to the literature on digitizing business networks, demonstrating that online activities can surpass traditional methods in effectiveness. The results are crucial for network development strategies, indicating that digital tools can replace and even outperform traditional working methods, offering new opportunities for maintaining and developing international business cooperation.